E-learning for the development of iot components in the post-covid-19 era - Rivera, Yair; Simancas, Ricardo; Vega, Elmer (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The challenge of educational systems has been to propose virtual scenarios with efficient mediation of technology that facilitate the evidence of technological development. Our proposal aims to define a learning strategy that allows technological development using IoT-based simulators and the interaction of cloud servers for data storage. It is intended to turn the instructor into a specialised guide, verifying the learning results. The proposal facilitates the development of computational competencies focused on technological creation with dynamic and configurable scenarios accessible from the web.